2012
DOI: 10.1111/jen.12021
|View full text |Cite
|
Sign up to set email alerts
|

SIMAGRIO‐W: Development of a prediction model for wireworms in relation to soil moisture, temperature and type

Abstract: As a result of increasing cultivation of corn and potatoes, the polyphagous larvae of the click beetles (Coleoptera: Elateridae), called wireworms, become a problem in agriculture (Parker and Howard 2001). The hypothesis that the vertical distribution of wireworms depends on soil moisture, soil temperature and soil type had to be verified. In field experiments, investigations on wireworm activity in relation to soil moisture and soil temperature were carried out over a period of 2 years. Bait traps were buried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 11 publications
2
35
0
1
Order By: Relevance
“…To our knowledge, no previous studies have shown any influence of soil texture only on wireworm damage. Jung et al (2012) studied the soil type in interaction with soil moisture and showed that the moisture preference of wireworms depended on the type of soil in which they are found. Using this interaction, a model was built on the presence or absence of larvae in upper soil profile with a prediction accuracy of about 80 %.…”
Section: Effect Of Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no previous studies have shown any influence of soil texture only on wireworm damage. Jung et al (2012) studied the soil type in interaction with soil moisture and showed that the moisture preference of wireworms depended on the type of soil in which they are found. Using this interaction, a model was built on the presence or absence of larvae in upper soil profile with a prediction accuracy of about 80 %.…”
Section: Effect Of Soil Propertiesmentioning
confidence: 99%
“…In Europe, they generally migrate twice a year, in spring and in autumn, when abiotic conditions are favorable in the upper soil layers (Jung et al 2012;Miles 1942), making them vulnerable to tillage at this period. Tillage reduces populations of eggs and young larvae by damaging them mechanically.…”
Section: Introductionmentioning
confidence: 99%
“…More information on oviposition preferences of aboveground adult stages in general is required in order to understand how this affects the distribution and abundance of larval stages belowground (Traugott et al, 2015). As with Bibionidae (Blackshaw and D'Arcy-Burt, 1993), the capture of wireworms can be affected by sampling method (Benefer et al, 2012), and as with many other soil taxa, timing of sampling can also impact upon the number of individuals recovered since a number of abiotic factors, temperature, and moisture in particular, alter activity and movement in the soil, both horizontally (Lafrance, 1968;Fisher et al, 1975) and vertically (Jung et al, 2014). In comparison to the findings of Benefer et al (2010) at least, this may account for some of the differences in abundance and composition, since sampling was carried out earlier (from January to March) in that study.…”
Section: Discussion Abundance and Community Compositionmentioning
confidence: 99%
“…For pest management, in particular, having information on all important influencing factors and their spatio-temporal interactions would help in predictive modeling of abundance and distributions (and ultimately crop damage and reduction of pesticide usage). More sophisticated models are now being produced for some taxa (e.g., wireworms; Jung et al, 2014) that are taking some of these factors into account, but there are still gaps in our knowledge concerning effects across time and space for different species.…”
Section: Effects Of Scale Spatial and Biotic Variables On The Distrmentioning
confidence: 99%
“…Carbon dioxide is emitted from germinating seeds and other plant tissues, and CO 2 gradients are therefore a basic means of orientation of insect larvae towards potential food sources (Doane et al 1975;Klingler 1957). These gradients have been shown to influence the vertical migrations of wireworms in soil (Jung et al 2014;Sonnemann et al 2014). In our experimental set-up, the germinating oat seedlings also produced CO 2 , and potentially attracted wireworms into conidia-contaminated soil layers.…”
Section: Treatmentmentioning
confidence: 99%